2021
DOI: 10.1007/s12119-021-09855-4
|View full text |Cite
|
Sign up to set email alerts
|

Gender Differences in Estimates of Love Styles for Self and Others

Abstract: This study investigated gender differences in how people estimate the intensity and style of love in themselves and in others. The six orientations toward love analyzed were: Eros (sex and passion), Ludus (game-playing), Storge (friendship and intimacy), Pragma (practical ventures), Mania (obsession and possessiveness), and Agape (altruistic love). The sample included 265 students (170 females and 95 males). Respondents evaluated their parents', romantic partners', and own overall love and the six love styles.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 43 publications
0
12
0
Order By: Relevance
“…Several studies were conducted related to the subject of the current study or one of its variables. One of them is the study by Neto (2021), which examined gender differences in how people estimate the intensity and style of love in themselves and in others. The six domains analyzed toward love were: sex and affection, play, friendship and intimacy, practical enterprise, obsession and possession, and altruistic love.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Several studies were conducted related to the subject of the current study or one of its variables. One of them is the study by Neto (2021), which examined gender differences in how people estimate the intensity and style of love in themselves and in others. The six domains analyzed toward love were: sex and affection, play, friendship and intimacy, practical enterprise, obsession and possession, and altruistic love.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Regarding gender differences, consistent findings on romantic experience and love styles are lacking. However, Neto (2021) suggests that women may be more willing to engage in unconditional and love-oriented approaches, emphasizing intimacy and mutual commitment. On the other hand, Regan (2016) found that men tend to hold more romanticized views of relationships and are more accepting and understanding of their partners.…”
Section: Love Well-being and Agingmentioning
confidence: 99%
“…This study uses a distinct insight in how persons estimate their own and other's love. Whereas a number of works have studied the love of one person toward another (Hendrick & Hendrick, 1992;Karandashev et al, 2020;Rubin, 1970;Sternberg & Barnes, 1988), only scarce research has approached the love estimates of others' love (Neto, 2021a;2021b).…”
mentioning
confidence: 99%
“…As far as we know, only two studies have been done on SEL (Neto, 2021a;2021b). In the Neto's (2021a) study females provided estimates of their own, their romantic part ner's and their parents' overall love and several varieties of love.…”
mentioning
confidence: 99%